TENSILE AND HARDNESS PROPERTIES OF KENAF-PP/PLA COMPOSITE FILLED NANOCLAY - Azmi, M.N; Rafeq, Saleman Abdul; Nadlene, Razali; Irwan, M.A.M; Aishah, A.M. (2013)
Different amount of nanoclay will be added to the binder of Kenaf fiber composite material in order to investigate the effect of nanoclay loading in the conventional polymer based composite material. The samples were prepared by using the internal mixing technique with constant composition of PP and PLA as the matrix constituent and 40wt% of kenaf fiber. Then, the nanoclay was added into the mixture with different amount, 1wt%, 3 wt% and 5 wt% respectively. Tensile test, hardness test and liquid immersion test were carried out for each sample. Result for tensile test shows increasing of nanoclay loading in the composite cause the decreasing tensile properties. However, 1wt% of nanoclay amount in the composite increases the Young Modulus about 15%. This is supported by the hardness test and liquid immersion test results where the sample with 1wt% of nanoclay shows better result compared to the other specimens.